DIFFERENT SUPPLEMENTS FOR FINISHING OF NELLORE CATTLE ON DEFERRED Brachiaria decumbens PASTURE DURING THE DRY SEASON - Andrade, Antonio Tadeu de [UNESP]; Rossi, Rodrigo Cesar; Stival, Vinicius Pissinati; Oliveira, Emanuel Almeida de [UNESP]; Moraes Sampaio, Alexandre Amstalden [UNESP]; Rosa, Bruna Laurindo [UNESP] (Inst Zootecnia, 2015)
This study evaluated the effect of four types of supplement on the finishing of Nellore cattle on deferred Brachiaria decumbens pasture during the dry season. Sixty-four castrated Nellore males with an age of approximately 34 months and initial body weight (BW) ranging from 360 to 380 kg were divided into 16 animals per treatment in a completely randomized design. The treatments consisted of four types of pasture supplement: deferred Brachiaria decumbens pasture + energy protein mineral salt (SuEPM) used as control; deferred Brachiaria decumbens pasture + urea + cottonseed meal (28% CP) + ground corn grain (SuCo); deferred Brachiaria decumbens pasture + urea + cottonseed meal (28% CP) + citrus pulp (SuCPu); deferred Brachiaria decumbens pasture + urea + cottonseed meal (28% CP) + soy hull (SuSH). The pasture was deferred for 170 days and provided 3,482 kg DM/ha of forage, permitting a stocking rate of 1.56 AU/ha (DM intake of 2.25% BW and 50% pasture efficiency). The animals received the supplement ad libitum in the SuEPM treatment and as % BW in the other treatments from July to October. The animals were slaughtered at a minimum BW of 457 kg. The following variables were evaluated: final weight, weight gain during the period (WG), average daily gain (ADG), hot carcass weight (HCW), and hot carcass yield (HCY). With respect to final weight, the supplement in the SuCo, SuCPu and SuSH treatments permitted a greater supply of nutrients and the animals therefore exhibited better performance (P<0.05) compared to the SuEPM treatment (mean of 478.68 vs 412.62 kg). The same effect was observed for the other parameters studied. Analysis of WG and ADG showed that SuSH was superior to the SuCo and SuCPu treatments (P<0.05) due to the increased offer of concentrate and SuEPM was inferior to the other treatments. Higher HCW (260.05 kg) and HCY (53.92%) were obtained with treatment SuSH as a result of greater performance. Supplementation of cattle during the dry period on deferred pasture with corn, citrus pulp and soy hull, offered at > 1.0% BW, promotes expressive weight gains that permit the animal to reach slaughter weight faster. The offer of supplements below 0.5% BW on deferred pasture for use during the dry period is not sufficient to promote satisfactory weight gains that would permit the animal to reach slaughter weight.
Keywords: soy hull; deferred pasture; dry season; citrus pulp; supplementation